1976
DOI: 10.1084/jem.144.6.1707
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation across the histocompatibility barrier: H2d T cells primed to antigen in an H-2d environment can cooperate with H-2k B cells.

Abstract: H-2d spleen cells derived from either tetraparental or semiallogeneic radiation bone marrow chimeras can be primed to antigen within H-2d recipients to generate helper T cells capable of cooperating in a secondary response with equal efficiency with H-2d or H-2k B cells. Thus it would seem that the cooperative act between T and B cells does not require that the T cell interacts with its target B cells by either cell interaction genes or via an altered self mechanism involving both antigen and the target B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…(Table X) that when antigen-primed helper T cells were derived from TBMC then these cooperated most efficiently with histoincompatible B cells, thus apparently excluding a requirement for T and B cells to share matching Cell Interartion gene products. For example, (Table XI) when we assayed the cooperative function of Summary of data of Waldmann et al (1976d). More recently similar results have been obtained with H-2'' T cells derived from H-2'' + H-2^ TBMC, which were able to cooperate effectively with H-2B cells (Table XI).…”
Section: The Use Of Bone Marrow Chimeras As Sources Of T Helper Cellssupporting
confidence: 68%
See 2 more Smart Citations
“…(Table X) that when antigen-primed helper T cells were derived from TBMC then these cooperated most efficiently with histoincompatible B cells, thus apparently excluding a requirement for T and B cells to share matching Cell Interartion gene products. For example, (Table XI) when we assayed the cooperative function of Summary of data of Waldmann et al (1976d). More recently similar results have been obtained with H-2'' T cells derived from H-2'' + H-2^ TBMC, which were able to cooperate effectively with H-2B cells (Table XI).…”
Section: The Use Of Bone Marrow Chimeras As Sources Of T Helper Cellssupporting
confidence: 68%
“…When this experiment was performed it was found that H-2'' spleen T cells derived from chimeric (H-2'' -I-H-2*') mice could, after priming in an H-2'' environment still cooperate efficiently with both H-2'' and H-2^ B cells (Waldmann et al 1976d). If this were the simple explanation then one would predict that if chimeric T cells of one parental type (say H-2'') were transferred into syngenic (H-2'^) recipients and primed there for the first time, then these cells should cooperate only with H-Z", and not H-2^ B cells.…”
Section: The Relevance Of the Priming Environment To T-b Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the in vivo studies with Fj -> BIO and Fj ->-AJ chimeras showed that T memory cells from those animals still showed haplotype preferences, even when transferred to and primed in (BIO X AJ) Fj irradiated recipients where an abundance of Fj macrophages are available for antigen presentation. Second, our previous studies with this in vitro system suggest that T-helper cells are monogamous, i. e. help one or very few B cells (Waldmann et al, 1976, Phillips & Waldmann, 1977. This finding is incompatible with any model that implies that T helper memory cells are activated by antigen presenting macrophages to release widely diffusible specific helper factors, but rather emphasises the need for T-and B-cells to be close if not in actual contact, to achieve cooperation.…”
Section: Discussionmentioning
confidence: 88%
“…Thelper cell function was then assessed 7 days later on A and B B-cells. This sort of experiment had given somewhat ambiguous results in our earlier studies (Waldmann et al, 1976). In brief, we had observed that Balb/c spleen cells from Balb/c -^ (Balb/c X C3H/He) F^ single or Balb/c + C3H/He ^ (Balb/c X C3H/He) Fj double chimeras could, after adoptive priming in a syngeneic (Balb/c) environment, cooperate with both Balb/c and CBA B-cells.…”
Section: The Relevance Of Priming Environmentmentioning
confidence: 83%